Numerical studies on smoke spread in the cavity of a double-skin façade - Ji, Jie; Li, Yi Fan; Shi, Wen Xi; Sun, Jin Hua (Journal of Civil Engineering and Management, 2016)
In this paper, influence of two key factors, fire room height and outer pane tilt angle, on smoke spread in the cavity of a double-skin façade (DSF) was studied numerically. The fire room was located adjacent to the DSF on the 2nd, 4th and 6th floors, respectively. The outer pane tilt angle varied at 80°, 90° and 100°. All cases were under two fire heat release rates of 1 MW and 5 MW. Results suggested that fire room height and outer pane tilt angle had significant effects on smoke spread in the cavity. For different fire room heights, there were two markedly different scenarios of smoke spread in the cavity between two vertical panes in a high-rise building. For outer pane tilt angle, the DSF with an inward tilted or vertical outer pane was dangerous for the upper floors due to hot smoke adhering to the upper inner pane. However, the turbulent vortex in the DSF with an outward tilted outer pane prevented hot smoke flowing out from the fire room.First published online: 24 Aug 2015